A facile and simple microwave-assisted synthesis method for mesoporous ultrathin iron sulfide nanosheets as an efficient bifunctional electrocatalyst for overall water splitting. Issue 16 (5th April 2022) - Mushtaq, Nouraiz; Wang, Zhitao; Tabassum, Hassina; Tahir, Muhammad; Han, Zhanli; Zhu, Youqi; Younas, Waqar; Ma, Xilan; Cao, Chuanbao
Abstract : The engineering of efficient electrodes is highly desired for full water splitting devices. Abstract : The engineering of inexpensive, high-efficiency and stable electrodes related to both the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is highly desired for full water splitting devices to promote future advances in this energy technology. Therefore, a large surface area, rich in exposed surface atoms, and mesoporosity are very effective parameters in electrochemical reactions. Herein, we have, for the first time, synthesized free-standing mesoporous Fe3 S4 nanosheets with a large surface area of 129.65 m 2 g −1 through a microwave-assisted synthetic technique. Our present synthesis strategy demonstrates a facile and cost-effective method to overcome the obstacles of fabricating ultrathin two-dimensional graphene-like transition metal sulfide nanosheets. The as-synthesized Fe3 S4 nanosheets are applied as both cathodic and anodic electrodes for full water electrolysis. Remarkably, Fe3 S4 nanosheets can exhibit a small overpotential ( η = 103 mV) to provide the required 10 mA cm −2 current density during the HER process. Meanwhile, a low overpotential of 230 mV is also exhibited for the OER process to allow a 10 mA cm −2 current density. Furthermore, the assembled full water splitting device can achieve potentials of 1.43 and 1.65 V at 10 and 100 mA cm −2 current densities, respectively, in an alkaline electrolyte with excellent cycling stability over 24 h. Our current study may provide an advanced channel for transition metal sulfide catalysts towards commercial water splitting applications.